Diagnostic method-based underestimation of leptospirosis in clinical and research settings; an experience from a large prospective study in a high endemic setting - Warnasekara, Janith; Srimantha, Shalka; Kappagoda, Chamila; Jayasundara, Dinesha; Senevirathna, Indika; Matthias, Michael; Agampodi, Suneth; Vinetz, Joseph M. (PLoS neglected tropical diseases, 2022)
Leptospirosis has globally significant human mortality and morbidity, yet estimating the clinical and public health burden of leptospirosis is challenging because timely diagnosis remains limited. The goal of the present study was to evaluate leptospirosis undercounting by current standard methods in both clinical and epidemiological study settings. A prospective hospital-based study was conducted in multiple hospitals in Sri Lanka from 2016 to 2019. Culture, whole blood, and urine samples were collected from clinically suspected leptospirosis cases and patients with undifferentiated fever. Analysis of biological samples from 1,734 subjects confirmed 591 (34.1%) cases as leptospirosis and 297 (17.1%) were classified as "probable" leptospirosis cases. Whole blood quantitative PCR (qPCR) did identify the most cases (322/540(60%)) but missed 40%. Cases missed by each method include; urine qPCR, 70% (153/220); acute sample microscopic agglutination test (MAT), 80% (409/510); paired serum sample MAT, 58% (98/170); and surveillance clinical case definition, 53% (265/496). qPCR of negative culture samples after six months of observation was of diagnostic value retrospectively with but missed 58% of positives (109/353). Leptospirosis disease burden estimates should consider the limitations of standard diagnostic tests. qPCR of multiple sample types should be used as a leading standard test for diagnosing acute leptospirosis.